(3OQGSI MGdI eDSSGJ NOeGJ Gdfbd GdLhj HGdLRGFQs - (3SajGf(B, (3MeGOhTs ((3GdLRGFQ(B:s (3OGQ gheI(B,s, 2019)
(3eaghe GdJShjb aj GdbQf GdhGMO hGdYTQjf hbjeI hQVG GdRHhf hGdLhOI, cPdc GdJhLgGJ GdMOjKI dGOGQI GdJShjb eY CHYGOg GdTGedI HVQhQI GdJQcjR Ydi GdehGQO aj JShjb GdNOeGJ ef hLgI fXQ JShjb GdYdGbGJ, HGdGVGaI Gdi eJWdHGJ fLGMgG eY CgejI JcfhdhLjG GdeYdheGJ hGdGJUGdGJ(B.(3GdJShjb GdOGNdj Heagheg hCgejJg hGdOhQ GdGSJQGJjLj dg(B. (3cPdc JShjb GdNOeGJ HWHjYI hNUGFU GdNOeI hCUfGa GdeRjL GdNOej eY GfJGLjI GdNOeI h KbGaI GdLhOI hHGdJGdj CgejJgG aj JMbjb aYGdjI GdGSJQGJjLjI hGdNWhGJ GdaYGdI dGOGQI GdJZjjQ(B. (3heOi JMbjb GdJhLg HGdJShjb GdTGed ef efXhQ KbGaI GdLhOI s
(3eQGLY U(B.339- 355 (3edGMb U(B.359- 407s
Keywords: (3GdJShjb Gdcdjs; (3JShjb(B- (3eDSSGJs